Development of a workplace breastfeeding support practice model in South Africa - Daniels, Lynette Carmen; Mbhenyane, Xikombiso Gertrude; Du Plessis, Lisanne Monica (International breastfeeding journal, 2024)
Background Globally, mothers have identified work as one of the main obstacles to exclusive and continued breastfeeding. The support a woman receives in her workplace in terms of workplace arrangements can be critical to enable women to continue breastfeeding. This study aimed to develop and assess the face validity of a practice model to support exclusive and continued breastfeeding in workplaces in the Western Cape, South Africa. Methods An explanatory, sequential, mixed-method research design, was conducted (June 2017 to March 2019) in three distinct phases. Phase one employed a quantitative, descriptive, cross-sectional study design. Phase 2 used a qualitative, multiple case study. Phase three involved the development and face validity of a practice model to support exclusive breastfeeding in workplaces. The face validity included two Delphi rounds for experts to provide input on the draft practice model. This paper will only report on phase 3 of the study. The practice model was developed, drawing on the analysis of data from phases one and two and using programme theory approaches and a logic model. Results The practice model was positively perceived. Participants viewed it as informative, well designed and easy to follow, even for those not knowledgeable about the subject. It was viewed as an ideal tool, if accompanied by some training. Participants were positive that the model would be feasible and most commended the tiered approach to implementation. They felt that workplaces would be more open to a step-by-step approach to implementation and if only a few activities are implemented it would be a start to make the work environment more conducive for breastfeeding employees. There were mixed opinions regarding commitment; a few participants mentioned commitment as a challenge they anticipated in the male-dominant environments in which they worked. The provision of space for breastfeeding at the workplace was also highlighted as a potential challenge. Conclusions Advocacy around creating an enabling workplace environment for breastfeeding is needed. The practice model has the potential to be internationally relevant, locally applied and may be of particular use to workplaces that want to initiate and/or strengthen breastfeeding support.